Future Caregiving Responsibilities, Employment Uncertainties, and Expected Childbearing Behavior: Survey Experimental Evidence from Germany - Vincent Jerald Ramos; Michaela Kreyenfeld; Enrique Alonso-Perez; Paul Gellert; Jan Paul Heisig; Julie Lorraine O'Sullivan (Population Research and Policy Review, 2025)
In societies experiencing declining birth rates, understanding factors that influence childbearing decisions is of interest. We used a factorial survey experiment to investigate how scenarios of future caregiving responsibilities toward aging parents and employment uncertainties shape the expected childbearing behavior of a fictitious couple. Respondents from the nationally representative German Socio-Economic Panel Innovation Sample (SOEP-IS) ( n 0.167em=0.167em1,750) were randomly assigned to five vignettes, each describing a hypothetical couple with varying levels of caregiving responsibilities towards an aging parent and employment uncertainties. Respondents subsequently rated their expectations about the hypothetical couple's childbearing behavior within the next three years using an 11-point scale. Results show that high caregiving responsibilities and dual employment uncertainties reduce expected childbearing behavior by 2.8 and 1.9 units respectively, compared to when these are absent. The negative effect of high caregiving responsibilities is more pronounced among women, while respondents' own caregiving and employment experiences do not moderate these effects. These results demonstrate how both future-oriented caregiving responsibilities and employment uncertainties alter expectations about family formation and highlight the scenarios that are regarded as more or less favorable for childbearing.
Keywords: 300; Caregiving responsibilities; Employment uncertainties; Expected childbearing; Factorial survey experiment; Germany